2022
DOI: 10.1177/02654075221110626
|View full text |Cite
|
Sign up to set email alerts
|

Social support and positive future expectations, hope, and achievement among Latinx students: Implications by gender and special education

Abstract: A cultural-ecological approach posits that multiple sources of relational support can contribute to youths’ strengths development. Some such strengths are positive future expectations (PFE) and hope, both of which represent beneficial, future-oriented cognitive-motivational constructs; however, they have not been fully explored among Latinx youth. Furthermore, it is unknown how different socializing agents (i.e., family, teachers, friends) influence youths’ PFE, hope, and academic achievement, and if relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 71 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…In the two southwest U.S. samples, aspects of peer relationships were examined as contributors to mental health, future expectations, hope, and academic achievement; these links were also examined by youths' age, gender, special education designation. Fraser et al (2022) found that friend support was less salient compared to their other sources of support, as friend support was not found to be related to any of the outcomes, except when examining the links for youth who had a special education designation. However, from the Fraser et al (2022) study, there was an unexpected finding in that friend support negatively predicted academic achievement, a finding the authors suggest is due to the possible low quality of those relationships for youth with learning disabilities.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…In the two southwest U.S. samples, aspects of peer relationships were examined as contributors to mental health, future expectations, hope, and academic achievement; these links were also examined by youths' age, gender, special education designation. Fraser et al (2022) found that friend support was less salient compared to their other sources of support, as friend support was not found to be related to any of the outcomes, except when examining the links for youth who had a special education designation. However, from the Fraser et al (2022) study, there was an unexpected finding in that friend support negatively predicted academic achievement, a finding the authors suggest is due to the possible low quality of those relationships for youth with learning disabilities.…”
mentioning
confidence: 89%
“…Fraser et al (2022) found that friend support was less salient compared to their other sources of support, as friend support was not found to be related to any of the outcomes, except when examining the links for youth who had a special education designation. However, from the Fraser et al (2022) study, there was an unexpected finding in that friend support negatively predicted academic achievement, a finding the authors suggest is due to the possible low quality of those relationships for youth with learning disabilities. Similarly, Padilla et al (2022) found only one significant association for peer constructs; they found that youth who reported more conflict with their best friend, on average, also reported more risky behavior.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Though not specific to science education, researchers have found that Latinx parents’ support their female and male children differently with regard to education. In a sample of 5th−12th grades Latinx students and their parents, familial support was related to boys’ positive future expectations for work and education, self-satisfaction, and hope in the context of their education, but not for girls (Fraser et al, 2022). Others have found that Latinx parents sometimes discourage or are reluctant to allow their Latina daughters to enroll in college (Cauce & Domenech-Rodriguez, 2002; Gonzalez et al, 2020) and that Latino boys receive more parental support for higher education than Latina girls (Cauce & Domenech-Rodriguez, 2002).…”
Section: Theoretical Frameworkmentioning
confidence: 99%